2015
DOI: 10.2215/cjn.08830914
|View full text |Cite
|
Sign up to set email alerts
|

Nonesterified Fatty Acids and Cardiovascular Mortality in Elderly Men with CKD

Abstract: Background and objectives Although nonesterified fatty acids (NEFAs) are essential as energy substrate for the myocardium, an excess of circulating NEFAs can be harmful. This study aimed to assess plausible relationships between serum NEFA and mortality due to cardiovascular disease (CVD) in individuals with CKD.Design, setting, participants, & measurements This was a prospective cohort study from the third examination cycle of the Uppsala Longitudinal Study of Adult Men, a population-based survey of 1221 elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“… 16 , 17 , 18 , 19 , 20 , 21 The supporting data include the observation that CKD patients have elevated NEFA concentrations, an independent predictor of all-cause and cardiovascular death. 21 Furthermore, CKD patients have perturbed circulating adipokine concentrations 18 , 20 and increased systemic inflammation that correlates with fat mass. 16 Indeed, visceral fat mass in peritoneal dialysis patients is an independent predictor of vessel dysfunction and therefore a risk factor for CVD.…”
mentioning
confidence: 94%
“… 16 , 17 , 18 , 19 , 20 , 21 The supporting data include the observation that CKD patients have elevated NEFA concentrations, an independent predictor of all-cause and cardiovascular death. 21 Furthermore, CKD patients have perturbed circulating adipokine concentrations 18 , 20 and increased systemic inflammation that correlates with fat mass. 16 Indeed, visceral fat mass in peritoneal dialysis patients is an independent predictor of vessel dysfunction and therefore a risk factor for CVD.…”
mentioning
confidence: 94%
“…Free fatty acids (FFAs) are intermediate products of lipid mobilization that result principally from lipolysis and the breakdown of triglycerides (TGs) (Stich and Berlan 2004). Previous studies have reported that FFA levels are associated with unfavorable functional outcomes in stroke and cardiovascular disease and may play a role in the process of disease progression (Choi et al 2014;Sun et al 2015;Xiong et al 2015;Duan et al 2017;Han et al 2018). In clinical work, we found that in some cancer patients, the FFA level was elevated even when TGs and total cholesterol (TCHO) were normal, and a high FFA level may be the only abnormality in biochemical tests.…”
Section: Introductionmentioning
confidence: 99%
“…Free FA accumulation is associated with CVD risk and mortality. In a prospective cohort study including 1221 elderly men in Sweden, increased free FA levels are associated with the risk for cardiovascular mortality in patients with CKD [ 98 ]. Even in patients who underwent kidney transplantation, CVD is still a major cause of post-transplantation mortality.…”
Section: Blood or Tissue Fas As Predictors For The Risks Of Cvd Anmentioning
confidence: 99%